Evaluating the Cellophane Production Supply Chain Using Multi-Criteria Decision-Making Approaches - َAhmad Jafarnejad; Amir Mohammad Khani (پژوهش در مدیریت تولید و عملیات)
Purpose: The supply chain of cellophane includes an independent set of parts whose relationship has to be properly managed to ascertain efficiency, performance, and sustainability. This research aims to provide detailed information regarding the cellophane supply chain and, using the Supply Chain Operations Reference model, act as a benchmark to enhance the adaptability and growth of the supply chain. Therefore, it can help the cellophane supply chain to remove its performance gap. Design/methodology/approach: Interpretive Structural Modelling (ISM) has been used along with the Multi-Criteria Decision-Making (MCDM) approaches, supported by the Analytic Network Process (ANP). ISM has been applied to analyze the interdependencies among different components of the supply chain; DANP has been implemented to prioritize the processes of the supply chain and potential suppliers. An investigation has been also performed on the intensity of influence and dependence among various methods in the supply chain. Findings: Findings indicated that the current market, demand, and competition are the biggest known factors impacting supply chain management. While this is more about learning the present state of the market, it is also important to realize future trends, customer needs, and competition. It includes information on marketing research, customer surveys, and competitive studies. A five-level hierarchical structure of the supply chain processes is reported, with levels one and five as the key drivers. The first level is wherein the market understanding, customer demand, and competitor practices are known. The fifth level involves the identification of potential risks and working out strategies to mitigate the risks. This level is all about active risk management. This involves developing ways through which contingency plans and strategies can be drafted to ensure the impact of the identified potential hazards is reduced. This level is so critical because it has a tremendous impact on performance and sustainability in the supply chain. Identifying potential risks and formulating strategies to reduce them are seen as independent variables with enormous impacts on other processes. These are very important processes as they could affect the effectiveness and efficiency of the entire chain. Both require careful management and continuous improvement to guarantee the smooth operation of the chain. Research limitations/implications: This study concentrated on possible constraints due to supply chain complexity and market changes. Since the cellophane supply chain is dependent on several factors, further research on optimization methods and improvement of decision-making processes can lead to more effective operational results. Practical implications: Findings are likely to give insight into the supply chain of cellophane, with an understanding of the market, customer demand, and competitive landscape. It also goes on to highlight potential risks, and the strategies formulated to reduce them. The use of the DANP technique helped rank the supply chain processes and identify potential suppliers, hence assisting in the effective allocation of needed resources such as materials, labour, and capital. This will assist those individuals concerned with the cellophane supply chain in the process of planning and making strategic decisions. This study contributes to the knowledge of SCM since it has elicited how much one needs to understand the market, manage risks, and ensure compliance. Social implications: Given the significance of sustainability and the need to lessen effects in the packaging sector, this study seeks to enhance procedures and mitigate risks, within the cellophane supply chain. Such efforts aim to safeguard the environment and uphold accountability. Originality/value: This study presented a comprehensive analysis and optimization of the cellophane supply chain using ISM and MCDM approaches. The new integrated approach of ISM and DANP helps to improve management processes and reduce supply chain risks.